Antibody responses to merozoite antigens after natural Plasmodium falciparum infection: kinetics and longevity in absence of re-exposure - Yman, Victor; Osier, Faith (BMC medicine, 2019)
Antibodies against merozoite antigens are key components of malaria immunity. The naturally acquired antibody response to these antigens is generally considered short-lived; however, the underlying mechanisms remain unclear. Prospective studies of travellers with different levels of prior exposure, returning to malaria-free countries with Plasmodium infection, offer a unique opportunity to investigate the kinetics and composition of the antibody response after natural infection.